Central Asia in Art From Soviet Orientalism to the New Republics - Abykayeva-Tiesenhausen, Aliya (I. B. Tauris & Company, Limited, 2016)
Cover -- Half-title -- Title -- Copyright -- Contents -- Acknowledgements -- Preface -- Map of Central Asia -- Introduction: Soviet Orientalism - The Untold Story -- Post-Soviet Art History and Theoretical Polemics -- Post-Soviet Art History and Material Images -- Postcolonialism in the Age of Petroleum -- Central Asia: Nationalism and Nation-Building -- Literature -- Personal Influences -- 1. The Politics of Multinationalism: Messages from the Centre -- The Union of Nations -- Nationality Policy -- The Great Russian People -- The Imperial Project and Soviet Art -- Russification -- Transformations -- Moscow and Muscovites -- Metro -- The War -- 2. Soviet Totalitarianism: The Visual Experiment -- Invented Doctrine and Exploitation of Visual Imagery -- Art Trapped within Gesamtkunstwerk -- Ideal Humans in the Multinational Context of the USSR -- 3. Teaching to See: Bringing Art to the Republics -- Central Asia and the Great Russian Brother -- Exploitation, Labour and Industry -- Semion Chuikov: Daughters of Soviet Kyrgyzia (or Lolitas of the Soviet East) -- Soviet Orientalism? Or Orientalism as Alternative? -- Pavel Benkov: Soviet Impressionism -- Alexander Volkov: Alternative East or Late Modernism -- Museumification of National Identity -- 4. Learning to be: The Natives Learn to paint, or the arrival of soviet identities -- National versus Soviet: from History to Everyday Life -- The Challenge to Tradition: the Patriarchal family versus the Soviet Friend -- Literacy, Language and Education -- Land, Agricultural Production and Nostalgia -- Abylkhan Kasteev: Primitive and National -- Ural Tansykbaev: Avant-garde Road to Socialist Realist Dream -- 5. De- Stalinisation and Beyond: Stalin to Borat -- After Stalin? -- From Kasteev to Meldibekov -- Central Asia, Soviet Art, Orientalism: Discourses and Images -- Notes -- Bibliographical References.